Chronic Helminth Infection Perturbs the Gut-Brain Axis, Promotes Neuropathology, and Alters Behavior. (15th February 2018) - Giacomin, Paul R; Kraeuter, Ann Katrin; Albornoz, Eduardo A; Jin, Shuting; Bengtsson, Mia; Gordon, Richard; Woodruff, Trent M; Urich, Tim; Sarnyai, Zoltán; Soares Magalhães, Ricardo J
Abstract : Helminth infections during childhood are associated with impaired learning ability. The present study demonstrates a potential mechanism by which worms influence cognitive function, via acute changes in the gut microbiome and lasting evidence of pathology in the brain tissue. Abstract: Helminth infections in children are associated with impaired cognitive development; however, the biological mechanisms for this remain unclear. Using a murine model of gastrointestinal helminth infection, we demonstrate that early-life exposure to helminths promotes local and systemic inflammatory responses and transient changes in the gastrointestinal microbiome. Behavioral and cognitive analyses performed 9-months postinfection revealed deficits in spatial recognition memory and an anxiety-like behavioral phenotype in worm-infected mice, which was associated with neuropathology and increased microglial activation within the brain. This study demonstrates a previously unrecognized mechanism through which helminth infections may influence cognitive function, via perturbations in the gut-immune-brain axis.